2012
DOI: 10.1158/1055-9965.epi-11-0644
|View full text |Cite
|
Sign up to set email alerts
|

Smoking Behavior and Exposure to Tobacco Toxicants during 6 Months of Smoking Progressively Reduced Nicotine Content Cigarettes

Abstract: Background Recent federal legislation gives the FDA authority to regulate the nicotine content of cigarettes. A nationwide strategy for progressive reduction of the nicotine content of cigarettes is a potential way to reduce the addictiveness of cigarettes, to prevent new smokers from becoming addicted and to facilitate quitting in established smokers. We conducted a trial of progressive nicotine content tapering over 6 months to determine the effects on smoking behaviors and biomarkers of tobacco smoke exposu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
177
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 143 publications
(192 citation statements)
references
References 22 publications
15
177
0
Order By: Relevance
“…While transdermal nicotine helps some smokers quit (eg, Stead et al, 2008), most who use nicotine replacement therapies eventually relapse, partly because they miss the behavioral and sensory aspects of smoking (Rose et al, 2000). Smoking cigarettes that deliver less than conventional doses of nicotine (ie,~1 mg/cigarette) reduce nicotine dependence (Benowitz et al, 2007;Benowitz et al, 2012;Benowitz et al, 2015) and promote smoking cessation when used with transdermal nicotine (Hatsukami et al, 2013). Further, a trial of reduced-nicotine cigarettes delivering~0.05-1.2 mg nicotine in 780 smokers showed decreases in nicotine dependence and cigarette consumption at 6 weeks compared to baseline (Donny et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…While transdermal nicotine helps some smokers quit (eg, Stead et al, 2008), most who use nicotine replacement therapies eventually relapse, partly because they miss the behavioral and sensory aspects of smoking (Rose et al, 2000). Smoking cigarettes that deliver less than conventional doses of nicotine (ie,~1 mg/cigarette) reduce nicotine dependence (Benowitz et al, 2007;Benowitz et al, 2012;Benowitz et al, 2015) and promote smoking cessation when used with transdermal nicotine (Hatsukami et al, 2013). Further, a trial of reduced-nicotine cigarettes delivering~0.05-1.2 mg nicotine in 780 smokers showed decreases in nicotine dependence and cigarette consumption at 6 weeks compared to baseline (Donny et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…We previously found that a reduction in nicotine content leads on average to minimal compensation and no increased exposure to tobacco smoke toxicants. 19,20 In this secondary analysis we analyzed baseline features of smoking to determine if they predicted those who responded differently to nicotine tapering in a 6-month study of nicotine reduction. We found that those with high nicotine dependence, as assessed by baseline FTCD, maintained differences in smoking behavior by smoking more cigarettes and exhibit greater smoke exposure (CO and PAHs) regardless of RNC level compared to those with low nicotine dependence.…”
Section: Discussionmentioning
confidence: 99%
“…Those who dropped out had a significantly higher level of dependence (FTCD). 19 It is possible that the dropouts tried to compensate for lower nicotine availability and were unsuccessful, leading to their dropping out. If so, the present analysis would underestimate the effect of dependence on compensation and does not identify the variables associated with this.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations